2019
DOI: 10.18632/aging.101814
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-derived extracellular vesicles for myocardial infarction: a meta-analysis of controlled animal studies

Abstract: Aims Stem cell-derived extracellular vesicles (EVs) have emerged as a promising therapy for myocardial infarction, but its effects remain incompletely understood. We aim to systematically review the efficacy of EVs on myocardial infarction in both small and large animals. Methods On April 5, 2018, we searched the PubMed, Embase and Web of Science databases using variations of “myocardial infarction” and “extracellular vesicle”. Controlled studies about the treatment eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…It reduces apoptosis, enhances cell proliferation, attenuates inflammatory responses, and induces angiogenesis (Alibhai et al 2018;Yang et al 2019). Several microRNAs (miR-126, 210, 146a, 19a, 21, 22) and bioactive molecules have been identified for such an action of the EVs (Alibhai et al 2018;Yang et al 2019). Further, microRNA-containing EVs have demonstrated atheroprotective activity.…”
Section: Extracellular Vesicles As a Therapeutic Candidate For Hgps?mentioning
confidence: 99%
“…It reduces apoptosis, enhances cell proliferation, attenuates inflammatory responses, and induces angiogenesis (Alibhai et al 2018;Yang et al 2019). Several microRNAs (miR-126, 210, 146a, 19a, 21, 22) and bioactive molecules have been identified for such an action of the EVs (Alibhai et al 2018;Yang et al 2019). Further, microRNA-containing EVs have demonstrated atheroprotective activity.…”
Section: Extracellular Vesicles As a Therapeutic Candidate For Hgps?mentioning
confidence: 99%
“…Thus, the balance between pro-coagulant and anti-coagulant properties of the platelet-derived vesicles plays an important role in supporting of hemostasis [24,25] . Intriguingly, there is evidence that the platelet-derived vesicles are cargo for several molecules, including chromatin, hormones, proteins, which mediate cell-to-cell cooperation, immune reaction, inflammatory response, and reparation [18][19][20][21][22] . It has been found that the main fraction of miRNA is localized in the platelet-derived vesicles, which protect miRNA from degradation in the circulation.…”
Section: Platelet-derived Vesiclesmentioning
confidence: 99%
“…The populations of the Figure 1. The proportions and functions of several types of extracellular vesicles in circulation [20][21][22][23] . APC: antigen presenting cells platelet-derived EVs may distinguish each other in not just their size and immune phenotype, but yet they can have a difference in a density (utilized as sucrose density gradient in ultracentrifugation), proteomic and lipidomic profiles [40] .…”
Section: Platelet-derived Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…4 | STEM CELL-DERIVED EVs IN MYOCARDIAL ISCHEMIAA meta-analysis indicated that stem-cell-derived EVs significantly reduce infarct size and improve cardiac function in an animal model of myocardial infarction 61. EVs from different MSC sources were found to protect cardiomyocytes from injury and boost angiogenesis [62][63][64].…”
mentioning
confidence: 99%